Grundtvig om samfundspagt, gensidig frihed og menneskerettigheder i ca. 1840: Med en kommenteret tekstudgivelse - Pedersen, Kim Arne (Grundtvig-studier, 2004)
Grundtvig om samfundspagt, gensidig frihed og menneskerettigheder i ca. 1840: Med en kommenteret tekstudgivelse[Grundtvig on the Social Contract, reciprocal Liberty and human Rights, c. 1840]By Kim Arne Pedersen In the current Danish debate, Grundtvig’s emphasis upon a fellowship of the folk [folkefællesskabet] is often perceived as standing in opposition to the idea of universal human rights as a foundational social concept. However, Grundtvig links together contract-theory and ideas upon liberty and upon human rights within his premise that every society, whether civic [borgerlig] or Christian, is founded upon a contract, a consensus which finds its expression in a covenant [,sammenfatning], a constitution [grundlov], which in Grundtvig’s view should be oral but which in his own writings can also be found in written form. This constitution comes about by the establishment of a pact [pagtsslutning], in the first place between God and man, creator and creature, thence in a derivative form in civic society between king and people. A society’s constitution expresses a dialogue-relationship between the two parties involved in the social compact, and upon this rests Grundtvig’s concept of dialogue-based liberty. The two-way I/you-relationship between God and man and between person and person is the basis of Grundtvig’s principle of freedom which Kaj Thaning concisely phrases thus: they alone are free who allow their neighbour to be free as well. On this principle of freedom rests Grundtvig’s concept of a pact, which is crucial to his notion of the Apostolic Creed as being the foundation of the Church and to his thinking on civic society. The Christian baptismal compact [dåbspagt] is entered into by God and man, the social compact in the first instance by king and people whose reciprocal freedom becomes the model for the citizens’ life with each other. This finds its expression in an oral English Summaries / danske resuméer but fixed agreement, a mutual pledge. The pledge binds fast the two parties to their rights and responsibilities and thus becomes the premise for Grundtvig’s Locke-inspired thinking on human rights. In the first transcribed text it is seen how Grundtvig incorporates human rights within an outline for a social constitution; and in the second text how, on the grounds of the oral and public character of the social compact, he rejects the Danish Royal Law [kongelov] of 1665, written down but at various times kept secret, as society’s foundation.